A new dynamic tactile display for reconfigurable braille: implementation and tests - Motto Ros, Paolo; Dante, Vittorio; Mesin, Luca; Petetti, Erminio; Del Giudice, Paolo; Pasero, Eros (Frontiers in Neuroengineering, 2014)
Different tactile interfaces have been proposed to represent either text (braille) or, in a few cases, tactile large-area screens as replacements for visual displays. None of the implementations so far can be customized to match users preferences, perceptual differences and skills. Optimal choices in these respects are still debated; we approach a solution by designing a flexible device allowing the user to choose key parameters of tactile transduction. We present here a new dynamic tactile display, a 8×8 matrix of plastic pins based on well-established and reliable piezoelectric technology to offer high resolution (pin gap 0.7 mm) as well as tunable strength of the pins displacement, and refresh rate up to 50 s-1. It can reproduce arbitrary patterns, allowing it to serve the dual purpose of providing, depending on contingent user needs, tactile rendering of non-character information, and reconfigurable braille rendering. Given the relevance of the latter functionality for the expected average user, we considered testing braille encoding by volunteers a benchmark of primary importance. Tests were performed to assess the acceptance and usability with minimal training, and to check whether the offered flexibility was indeed perceived by the subject as an added value compared to conventional braille devices. Different mappings between braille dots and actual tactile pins were implemented to match user needs. Performances of eight experienced braille readers were defined as the fraction of correct identifications of rendered content. Different information contents were tested (median performance on random strings, words, sentences identification was about 75%, 85%, 98%, respectively, with a significant increase, p< 0.01), obtaining statistically significant improvements in performance during the tests (p< 0.05). Experimental results, together with qualitative ratings provided by the subjects, show a good acceptance and the effectiveness of the proposed solution.